ISLAMIC EDUCATION ADMINISTRATION AND THE ART OF MANAGING IT - Amrullah, Abdul Malik Karim; Najihah, Iffatun (Idaarah: Jurnal Manajemen Pendidikan, 2022)
Optimal management of education administration becomes very significant in aligning itself with science and technology. This study aims to determine the concept of education administration, to know the function of education administration, to know the scope of education administration, to analyze the art of managing Islamic education administration. This research is a library research, where the author collects data from various references such as books, articles, and others. Data collection with reading and note-taking technique is the technique used by the author. In analyzing the data, the writer uses Miles and Huberman perspective analysis techniques, namely: 1) Data reduction; 2) Presenting data; 3) Drawing conclusions. The results of this article are: 1) An important point of an educational administration relates to the making of decisions and legislation on the maximum utilization of an organization; 2) Education administrators have three types of ethical responsibilities towards themselves, their organizations and society; 3) A good administrator of Islamic education must have knowledge and art of administration that refers to Islamic religious culture and ethics as the foundation for achieving the proposed goals and objectives.